Selective dorsal rhizotomy long-term effects on functional motility in Jordanian children with spastic cerebral palsy - Al-kharabsheh, Yazan E.; Said, Anas; Ismaiel, Ismail A.; Khawaja, Issam; Altaher, Marwan; Bani-Ahmed, Ali; Cirstea, Carmen M. (Frontiers in Neurology, 2025)
IntroductionSpasticity management in children with cerebral palsy (CP) is a challenge for healthcare providers worldwide. In the US and Europe, treatment options include non-surgical and surgical (i.e., selective dorsal rhizotomy, SDR) procedures, with beneficial effects on functional motility. SDR was introduced in Jordan in 2019. We performed the first assessment of the long-term effects on motor function in Jordanian children with spastic CP (SCP) who underwent SDR.MethodsA retrospective cohort study of 43 patients (28 boys, 15 girls, mean ± SD age at surgery, 6.2 ± 2.5 years, 67.4% with diplegia, 30.2% quadriplegia, and 2.3% hemiplegia, 97.7% bilateral deficits) who received SDR (42 bilateral) was conducted between 01/01/2019 and 03/01/2023. Gross Motor Function Classification System (GMFCS) and Functional Mobility Scale (FMS) scores were compared before and 12 months after SDR. Sex, age and clinical scores at surgery, and post-SDR surgical treatment were included in the model (IBM SPSS Statistics 29.0).ResultsClinical scores improved 12 months after SDR: GMFCS decreased by at least one level (in 58.5% of patients), and FMS significantly increased (p < 0.001); GMFCS decreased in 77.7% of those with pre-SDR severe impairment vs. 43.5% in moderately to mildly impaired patients. An age sub-analysis demonstrated higher changes in GMFCS in younger children (GMFCS decreased in 46.9% of those aged <10 years old vs. none in those older than 10 years). These findings suggest that younger children (<10 years old) and more impaired (levels IV and V on GMFCS) are likely the best candidates for this procedure. Twelve-month functional improvement was similar in boys and girls (GMFCS decreased in 44.0% of boys vs. 37.5% of girls). Compared to pre-SDR management, all patients continued physiotherapy, less received Botox (by 97.7%), and more received adjunct orthopedic surgeries (32.6% vs. none) after SDR; out of those receiving post-SDR adjuvant surgeries, 50.0% improved GMFCS (compared to 64.0% of those without).ConclusionOur data demonstrated SDR’s beneficial long-term effects on functional mobility in SCP children, particularly those younger than 10 years and more severely impaired. These findings provide critical information that may aid in identifying “the best” therapeutic window and “the best” candidate for SDR in Jordan.